2015
DOI: 10.1007/jhep07(2015)054
|View full text |Cite
|
Sign up to set email alerts
|

N = 2 $$ \mathcal{N}=2 $$ supersymmetric gauge theories on S2 × S2 and Liouville Gravity

Abstract: We consider N = 2 supersymmetric gauge theories on four manifolds admitting an isometry. Generalized Killing spinor equations are derived from the consistency of supersymmetry algebrae and solved in the case of four manifolds admitting a U(1) isometry. This is used to explicitly compute the supersymmetric path integral on S 2 × S 2 via equivariant localization. The building blocks of the resulting partition function are shown to contain the three point functions and the conformal blocks of Liouville Gravity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(85 citation statements)
references
References 38 publications
4
80
1
Order By: Relevance
“…For example, it would be interesting to compare our results with four-spins correlation functions in the Q-states Potts model for general values of Q. Our results may also have applications in four-dimensional gauge theories, in the context of their relation with Liouville theory with a central charge less than one [18,19].…”
Section: Resultsmentioning
confidence: 82%
“…For example, it would be interesting to compare our results with four-spins correlation functions in the Q-states Potts model for general values of Q. Our results may also have applications in four-dimensional gauge theories, in the context of their relation with Liouville theory with a central charge less than one [18,19].…”
Section: Resultsmentioning
confidence: 82%
“…As discussed in [22] (see also [23,63]), four-dimensional N = 2 supersymmetric theories can be placed on compact Euclidean manifolds with metric g µν if one can find symplectic-Majorana spinors ξ I andξ I solving the generalized Killing spinor equations…”
Section: A2 σ-Matrices and Fierz Identitiesmentioning
confidence: 99%
“…In this paper, we would like to derive a 4d-2d duality that has not yet been listed in [3,Introduction]. To this end, note that in [4], a supersymmetric theory was constructed on S 2 × S 2 , and its partition function was computed using the technique of localization. The authors observed that the building blocks of the partition function contained three-point functions and conformal blocks of Liouville gravity [5,6], and so they conjectured a novel AGT-like correspondence between the 4d supersymmetric theory on S 2 × S 2 and 2d Liouville gravity.…”
Section: Jhep05(2017)121mentioning
confidence: 99%
“…4 This amounts to inserting concrete values for the supergravity fields G and α, which emerged from reduction of the frame field in six dimensions. Then we solve this equation.…”
Section: Jhep05(2017)121mentioning
confidence: 99%
See 1 more Smart Citation